The Level of Conceptual Understanding of Functions and their Transformations and its Relationship with the Productive Motivation among Mathematics Students in the Faculty of Education University of Sana`a - Al-Mahab, AbdolRahman Ali Saleh; Saeed, Radman Mohamed (Journal of Educational and Psychological Sciences, 2023)
The study aims to investigate the conceptual understanding of functions and their transformations among Mathematics students in the Faculty of Education University of Sana`a, and to investigate the relationship between the productive motivation towards learning Mathematics among students and their performance on the conceptual understanding of functions test. The researcher adopted a comprehensive counting method for all the (25) students officially enrolled in the first level of the Mathematics Department for the 2021/2022 university year. The data was collected using two tools: one is a test to measure students' conceptual understanding, and the other is a measure of productive motivation. The results of the study showed a low level of conceptual understanding of students, with students' average performance on the test (1.24), and a low level of performance. However, there were no statistically significant differences in the conceptual understanding of functions due to the variables (gender, secondary school rate, place of obtaining it). The results also showed that there is a medium direct positive correlation between students' performance in the conceptual understanding test of functions and the productive motivation towards learning Mathematics.
Keywords: conceptual understanding; productive motivation; functions and their transformations